63-3x=11-9x

Simple and best practice solution for 63-3x=11-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 63-3x=11-9x equation:


Simplifying
63 + -3x = 11 + -9x

Solving
63 + -3x = 11 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
63 + -3x + 9x = 11 + -9x + 9x

Combine like terms: -3x + 9x = 6x
63 + 6x = 11 + -9x + 9x

Combine like terms: -9x + 9x = 0
63 + 6x = 11 + 0
63 + 6x = 11

Add '-63' to each side of the equation.
63 + -63 + 6x = 11 + -63

Combine like terms: 63 + -63 = 0
0 + 6x = 11 + -63
6x = 11 + -63

Combine like terms: 11 + -63 = -52
6x = -52

Divide each side by '6'.
x = -8.666666667

Simplifying
x = -8.666666667

See similar equations:

| 0x+11=71-3x | | 5x-94=2x-7 | | 4x-8-2x=x-2 | | 5(4-3)=19 | | 2(5-4)=2 | | 6x+2x^2+1=1 | | 2(30-12)=18 | | 4a^2+625b^4=0 | | 4n+55=8 | | x^4-4x^2+1=0 | | 26=6 | | 14-10x=36-24x | | 8x^4+28x^3-30x^2+11x-2=0 | | 3(6x-14)=12x+6(x-3) | | 1x+10=91+x | | 3(15+2x)-60+9x=0 | | 1.875x+2.125y=97.1 | | 2x+1/3=17 | | 2x+4d+6x-5c+4f= | | (x^2+x)(x+6)=7x | | 10x+30=8x+20 | | 2y-30=0 | | y=400+.25(0) | | y=400+.25(-1600) | | ln(5x-9)=1 | | 106-4x=14x+20 | | 228781=1010x-x^2 | | 5-7X=122-28X | | 1096x-x^2=268975 | | 78-2x=25x+18 | | 2190000=15000x+60000 | | 900000=15000x+60000 |

Equations solver categories